1. Use the Pythagorean Theorem since this is a right triangle:
a^2 + b^2 = c^2
3^2 + b^2 = 4^2
b^2 = 4^2 - 3^2
b = √ 7
b = 3
answer : 3
Answer:
<h3> FALSE</h3>
Step-by-step explanation:
The statement "The expression contains 2 terms." is false because the expression contains 3 terms: 7f, 15 and -2g
Answer:
The page numbers are 36 and 37.
Step-by-step explanation:
n + (n + 1) = 73
2n + 1 = 73
n = (73 - 1)/2
= 72/2 = 36
Answer:
$55,080
Step-by-step explanation:
Hope this helps.
3m² = 3 - 8m
0 = 3m² + 8m - 3
0 = (3m - 1 )(m + 3)
m = -3, 0.33